Technology trends for 2025 what O'Reilly learning platform usage tells us about where the industry is headed - Loukides, Michael Kosta (O'Reilly Media, Inc., 2025)
O'Reilly's 2.8+ million members don't spend their time chasing buzzwords, trends, or fads; they're putting the latest technology to work in organizations around the world day in and day out. So we can learn a lot from which tools they're interested in and what problems they're trying to solve. In his annual Technology Trends report, Mike Loukides scrutinizes the content our users are exploring, the skills they're seeking, and the questions they're asking to provide a snapshot of the industry--and the results are revealing. It's no surprise that AI continues to dominate the conversation this year, but a decline in interest in GPT hints at a more-even playing field. Security is up. Cloud is down. And that's just the start.
Includes bibliographical references
Keywords: Information technology -- Technological innovations